Aplicación móvil para entrenamiento, seguimiento y evaluación en medidas de seguridad de la información basada en la norma NTC - ISO /IEC 27001 (2021)
For the Colombian Institute of Family Welfare (hereinafter ICBF), Regional Meta, it has been a vitally important need that those who participate in its activities have knowledge of the NTC- ISO / IEC 27001-2013 standard, which has been adopted by ICBF and is reflected in the information security policy manual.